Reflections of Hospice Staff Members About Educating Hospice Family Caregivers Through Telenovela. (February 2021) - Cruz-Oliver, Dulce M.; Abshire, Martha; Budhathoki, Chakra; Oliver, Debra Parker; Volandes, Angelo; Smith, Thomas J.
Objective: Hospice family caregivers are seeking additional information related to patient care, pain and symptom management, and self-care. This study interviewed hospice staff about the potential dissemination of bilingual telenovelas to address these caregiver needs. Methods: Qualitative structured phone interviews were conducted with 22 hospice professionals from 17 different hospice organizations in 3 different Midwest states. The interviews were conducted from October to December 2019. Hospice staff volunteers were recruited from conferences, then individual interviews were audio-recorded, transcribed, and thematic analysis was conducted to gain an in-depth understanding of how to best implement telenovela video education into hospice care. Results: Most participants were hospice nurses (36%) located primarily in Missouri (91%), with a mean of 9 years of experience. Three discrete themes emerged, the educational resources currently provided to patient/families, perceptions of the usefulness of telenovelas for education, and practical suggestions regarding the dissemination of telenovelas. The development of 4 telenovela videos covering different topics is described. Conclusion: Hospice staff responded favorably to the concept of telenovelas and identified important keys for dissemination.